Center-Pivot-Irrigated Alfalfa Cost-Return Budget in Western Kansas - Dumler, Troy J.; O'Brien, Daniel M.; Olson, Brian L.S.; Martin, Kent L. (My University, 2011)
This publication projects a budget that reflects expected income and costs based on center-pivot-irrigated alfalfa production in western Kansas.
MF584_2011_12
Keywords: MF584; Economics; Crops; MF